2017
DOI: 10.1089/sur.2016.255
|View full text |Cite
|
Sign up to set email alerts
|

Specific Clinical Profile and Risk Factors for Mortality in General Surgery Patients with Infections by Multi-Drug–Resistant Gram-Negative Bacteria

Abstract: Multi-drug resistant infections in the surgical population are increasing. The most common clinical profile is a 65-year-old male, with previous comorbidities, who has undergone a surgical intervention, intensive care unit (ICU) admission, and invasive procedures and who has acquired the MDR infection in the nosocomial setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…In the present study, about three fourth samples showed growth of bacteria on culture which was similar to other studies. 9 , 10 The incidence of wound infection was higher in males (75%) than in females (25%) in the present study which was consistent with another study 11 which could be explained by the fact that males were more prone to develop wound infection perhaps due to study area was an orthopaedic hospital and males were mostly attacked by accidental injury by road traffic accident than female.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, about three fourth samples showed growth of bacteria on culture which was similar to other studies. 9 , 10 The incidence of wound infection was higher in males (75%) than in females (25%) in the present study which was consistent with another study 11 which could be explained by the fact that males were more prone to develop wound infection perhaps due to study area was an orthopaedic hospital and males were mostly attacked by accidental injury by road traffic accident than female.…”
Section: Discussionsupporting
confidence: 91%
“…The Enterobacteriaceae in an Indian outbreak in 2010 were resistant to all the available antibiotics, which attracted global attention [27]. On January 29, 2018, the World Health Organization (WHO) published monitoring data on bacterial resistance to antibiotics for the first time, which revealed that bacterial resistance was widespread, with serious bacterial infections and high drug resistance in both high- and low-income countries, and had become a major public health problem worldwide [28].…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies report [ 63 65 ], MDR-GNB causing pneumonia can be acquired from the community or hospital setting with risk factors including prolonged hospital stay, prior MDR-GNB colonization or infection, high frequency of antibiotic resistance in the setting, ICU admission, mechanical ventilation, and surgical intervention. They are also common in the elderly population, patients with prior antibiotic use, those with underlying pulmonary diseases (such as chronic obstructive pulmonary disease and bronchiectasis), diabetes mellitus, immunosuppressive conditions (like HIV and malignancies), prior hospitalization, and chronic alcoholism [ 66 70 ].…”
Section: Introductionmentioning
confidence: 99%